Enhancement of cucumber resistance under salt stress by 2, 4-epibrassinolide lactones - He, Xianxia; Wan, Zilong; Jin, Ning; Jin, Li; Zhang, Guobin; Lyu, Jian; Liu, Zeci; Luo, Shilei; Yu, Jihua (Frontiers in Plant Science, 2022)
This study investigated the effects of exogenous 2, 4-epibrassinolide lactone (EBR) on the growth, photosynthetic pigments, antioxidant defense system, ion homeostasis, MAPK cascade and key genes of SOS signaling pathway of cucumber seedlings under salt stress using cucumber "Xinchun 4" as the test material. The experiment was set up with four treatments: foliar spraying of distilled water (CK), 50 mmol.L-1 NaCl (NaCl), 50 mmol.L-1 NaCl+foliar spray of 0.01 mg.L-1 EBR (EBR+NaCl), and 50 mmol.L-1 NaCl+foliar spray of 2, 4 μmol.L-1 BRZ (BRZ+NaCl). The results showed that EBR+NaCl treatment significantly increased plant height, above-ground fresh weight, total root length, total root surface area, average rhizome and photosynthetic pigment content compared to NaCl treatment. Meanwhile, compared with NaCl treatment, EBR+NaCl treatment significantly increased superoxide dismutase, catalase and ascorbate peroxidase (SOD, CAT and APX) activities, significantly promoted the accumulation of osmoregulatory substances (soluble sugars and proline), and thus effectively reduced malondialdehyde (MDA) content and relative electrical conductivity of cucumber leaves. Exogenous spraying of EBR also significantly reduced Na+/K+ under NaCl stress, effectively alleviating the toxic effects of Na+ ions. In addition, exogenous EBR induced the up-regulated expression of CsMAPK3, CsMAPK4, CsMAPK6 and CsMAPK9 genes in the MAPK cascade signaling pathway and CsSOS1, CsSOS2 and CsSOS3 genes in the SOS signaling pathway to enhance salt tolerance in cucumber under NaCl stress. Therefore, exogenous spraying EBR may effectively reduce the damage of salt stress on cucumber seedlings by improving antioxidant capacity, maintaining ion homeostasis and activating salt-tolerant related signaling pathways, and promote the growth of cucumber seedlings and the establishment of root system morphology. This study may provide a theoretical basis for the sustainable production of cucumber under salt stress conditions.